Value creation in mergers and acquisitions. - Chua, Teck Keong. (2011)
The impact of takeovers in Singapore and Malaysia on shareholder wealth is studied and the relative performance of related vs. unrelated acquisitions is also investigated. Assuming efficient markets, such increases in shareholder wealth are a direct measure of value expected to be created from the acquisition. This study seeks to investigate the sources of such value. Based on past literature, two types of synergy are hypothesised to be available in acquisition as sources of value creation - operational and financial.Operational synergy appears in the form of post-acquisition increases in operating performance. Financial synergy according to the Debt Co-Insurance Hypothesis(Lewellen (1971)) is theorised to be in the form of post-acquisition increases in leverage.Another form of financial synergy comes about through the formation of internal capital markets by the acquirer who seeks a target that has a investment opportunities-cash resources mismatch position opposite to its own. Thus post-acquisition financial ratios and a variable representing the Internal Capital Markets Hypothesis investigated.